Experimental and Modeling Dynamic Study of the Indirect Solar Water Heater: Application to Rabat Morocco - Ouhammou Badr; Azeddine Frimane; Aggour Mohammed; Brahim Daouchi; Abdellah Bah; Halima Kazdaba (Institute of Advanced Engineering and Science, 2018)
The Indirect Solar Water Heater System (SWHS) with Forced Circulation is modeled by proposing a theoretical dynamic multi-node model. The SWHS, which works with a 1,91 m2 PFC and 300 L storage tank, and it is equipped with available forced circulation scale system fitted with an automated sub-system that controlled hot water, is what the experimental setup consisted of. The system, which 100% heated water by only using solar energy. The experimental weather conditions are measured every one minute. The experiments validation steps were performed for two periods, the first one concern the cloudy days in December, the second for the sunny days in May; the average deviations between the predicted and the experimental values is 2 %, 5 % for the water temperature output and for the useful energy are 4 %, 9 % respectively for the both typical days, which is very satisfied. The thermal efficiency was determined experimentally and theoretically and shown to agree well with the EN12975 standard for the flow rate between 0,02 kg/s and 0,2kg/s.